Photobiological hydrogen production: Recent advances and state of the art - Eroglu, Ela; Melis, A. (2011)
Photobiological hydrogen production has advanced significantly in recent years, and on the way to becoming a mature technology. A variety of photosynthetic and non-photosynthetic microorganisms, including unicellular green algae, cyanobacteria, anoxygenic photosynthetic bacteria, obligate anaerobic, and nitrogen-fixing bacteria are endowed with genes and proteins for H 2-production. Enzymes, mechanisms, and the underlying biochemistry may vary among these systems; however, they are all promising catalysts in hydrogen production. Integration of hydrogen production among these organisms and enzymatic systems is a recent concept and a rather interesting development in the field, as it may minimize feedstock utilization and lower the associated costs, while improving yields of hydrogen production. Photobioreactor development and genetic manipulation of the hydrogen-producing microorganisms is also outlined in this review, as these contribute to improvement in the yield of the respective processes. © 2011 Elsevier Ltd.